Jezikoslovni pogledi na trpnik v zgodovini slovenskega jezika - Leskovec, Mojca (Jezik in slovstvo, 2016)
The article explores the use of the passive voice in the Slovenian language, which is characterised by a longstanding tradition of rejection. This began with Vodnik and Šmigoc and escalated with Metelko, Janežič and the first grammar book by Breznik. The rejection of the passive voice subsequently ceased in Breznik's last grammar book and in grammar books by the Three authors, but it continued at least partially in the contemporary Slovenian grammar book, which states that in technical, popular and scientific texts it is not good to use the passive voice too often. Concerning the question of the passive voice, an analysis of grammar and orthography books as well as linguistic discussions indicated four periods of treatment in the history of the Slovenian language. An examination of textbooks and language discussion forums and an analysis of newspaper texts showed that in each of these periods the prescribed norm was passed to users and applied in practice.
Keywords: Slovene; slovenščina; verb; glagol; glagolski način; voice; trpnik; raba; zgodovinski pregledi; slovenske slovnice